Bank Media Pembelajaran dalam Pembelajaran IPS (Studi Kasus di Kelas 3 SDN Sungai Miai 5) - Pitaloka, Intan Diya; Astuti, Aulia Widi; Nursyipa; Ferdiyansyah, Aldy; Asniwati (BALE LITERASI, 2025)
Social Studies (IPS) learning at elementary school level often still relies on lecture methods and does not involve the use of learning media, making the learning atmosphere monotonous and less interesting. This has an impact on low student involvement and their understanding of the material presented. This study aims to describe the implementation of the Learning Media Bank as an innovative alternative in improving the quality of IPS learning in grade 3 of SDN Sungai Miai 5. The approach used is qualitative with a case study method. Data were collected through observation, interviews, and documentation involving teachers and students. The results of the study indicate that the Learning Media Bank, which contains concrete media such as physical teaching aids and digital media such as learning videos, simulations, and interactive presentations, is effective in increasing student learning motivation, active participation, and understanding. In addition, the existence of this media also helps teachers save preparation time and enrich learning strategies. Although there are still obstacles such as limited facilities and low digital literacy of some teachers, the Media Bank remains a relevant and useful solution for creating more interesting and contextual IPS learning.